Compliance with a Low Salt Diet in Elderly Hypertension at the Elderly Posyandu, Gedog Village, Sananwetan District, Blitar City - Ulfa Husnul Fata; Ayu Rahmawati; Wahyu Wibisono; Raden Roro Dewi Rahmawati Aktyani Putri (STIKes Patria Husada Blitar, 2023)
The problem of elderly hypertension is very complex, especially the problem of a low-salt diet. Non-compliance with hypertension will have a negative impact on the elderly and will cause many complications. This research is a descriptive study that aims to see the adherence to a low-salt diet in hypertensive elderly people. The population in this study were hypertensive elderly at the Srikandi elderly Posyandu and Brontoseno Elderly Posyandu in the Working Area of the Sananwetan Health Center, Gedog Village, Sananwetan District, Blitar City as many as 60 people. The sample in this study is based on the formula for calculating the number of samples, namely as many as 50 people. The sampling technique in this study was simple random sampling. The tools in this study were a respondent characteristics questionnaire and a low-salt diet adherence questionnaire that the researchers made themselves based on references. This research was conducted from April to May 2023. General data in this study included gender, marital status, last education, length of time suffering from hypertension and routine internal pressure control. While the specific data in this study is the adherence diet of hypertensive elderly. The results of this study indicate that almost half of the respondents are less compliant with the low-salt diet, namely 46% (23 respondents) and a small proportion of the respondents are compliant with the low-salt diet, 14% (7 respondents). Based on the results of this study, more in-depth interventions are still needed, especially to increase adherence to a low-salt diet in elderly hypertension